Who moved my goat cheese? - Cahoon, Lynn (Cahoon, Lynn. Farm-to-fork mysteries, 2018)
"With three weeks until opening night for their restaurant, the County Seat, Angie and her best friend and business partner Felicia are scrambling to line up local vendors--from the farmer's market to the goat dairy farm of Old Man Moss. Fortunately, the cantankerous Moss takes a shine to Angie, as does his kid goat Precious. So when Angie hears the bloodcurdling news of foul play at the dairy farm, she jumps in to mind the man's livestock and help solve the murder"--Back cover.